Lessons learnt in the response to COVID-19 in Mozambique: enabling readiness for the next pandemic - Posse, Mariana E.; Muriithi, Grace Njeri; Achala, Daniel Malik; Adote, Elizabeth Naa Adukwei; Mbachu, Chinyere Ojiugo; Beshah, Senait Alemayehu; Nwosu, Chijioke Osinachi; Ataguba, John Ele-Ojo (Frontiers in Health Services, 2025)
IntroductionThe coronavirus disease 2019 (COVID-19) has led to a dramatic loss of human lives worldwide and caused economic and social disruptions. The risk of another pandemic occurring is ever-present requiring countries to document factors that influenced the response to COVID-19 to guide the response to future pandemics. This study documents lessons learnt from Mozambique's COVID-19 response, considering the perspectives of various stakeholders and examining different components of the response.MethodsWe used a qualitative phenomenology research design and collected data using in-depth interviews. We used purposive sampling by selecting institutions with relevant experience and knowledge to inform the study objectives. We also used snowballing techniques by asking respondents for other potential informants. We interviewed 19 individuals indicated by the representatives of the institutions selected for the study. The institutions were mostly based in Maputo city, the country's capital. Participants were asked about their role in the organization; responsibility in vaccine distribution and delivery in Mozambique; their opinion on what worked well in the country's response to COVID-19, and what could be improved as preparation to future pandemics. Data was coded using a computer-assisted qualitative data analysis software Maxqda 2020 and analyzed using a deductive thematic approach. A validation meeting was held, in which research participants were asked to check the accuracy of the results and interpretations.ResultsKey drivers of the COVID-19 response were strong leadership; a clear plan and strategies; a functional coordination mechanism; the use of evidence to make decisions; a careful consideration of priority groups; investments in the supply chain and surveillance systems; the utilization of pre-existing vaccination structures; and partnership between the government and several stakeholders. There is room for improvement including the development of a clear budget, a communication plan, creation of an emergency fund, accountability in the use of funds, decentralization of surveillance infrastructure and representation of vulnerable, marginalized, and hard-to-reach populations in the design and implementation of pandemic response.ConclusionThe lessons learned from the COVID-19 response in Mozambique, which could be considered when preparing for an effective and equitable response to future pandemics, are in essence the following: there should be government leadership, a response plan, adequate resources, use of data to inform decisions, constant vigilance, a prompt response, involvement of all stakeholders and documentation of actions for continuous learning. These lessons could improve pandemic preparedness nationally and globally.